2021
DOI: 10.1002/er.6559
|View full text |Cite
|
Sign up to set email alerts
|

First‐principles study on structural, electronic, magnetic, elastic, mechanical and thermodynamic properties of Mn 2 PtCo Heusler alloy

Abstract: Summary The structural, electronic, magnetic, mechanical and thermodynamic properties of the Mn2PtCo Heusler alloy have been investigated in the frame work of density functional theory (DFT). The cohesive energies confirm the Cu2MnAl‐prototype structure of Mn2PtCo with the ferromagnetic phase. The spin polarized electronic band profile of the Mn2PtCo exhibits its metallic character by considering the generalized gradient approximation (GGA) and modified Becke‐Johnson (GGA‐mBJ) approximation in the calculations… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 28 publications
(13 citation statements)
references
References 94 publications
(119 reference statements)
2
11
0
Order By: Relevance
“…The equation (8) has been used to compute Y and a higher Y designates the material to be stiffed. Similar results were observed in [8,14,15,21], whereas higher values were surveyed in [16,17,19,20].…”
Section: Rhsupporting
confidence: 86%
See 1 more Smart Citation
“…The equation (8) has been used to compute Y and a higher Y designates the material to be stiffed. Similar results were observed in [8,14,15,21], whereas higher values were surveyed in [16,17,19,20].…”
Section: Rhsupporting
confidence: 86%
“…The lower shear modulus (42.6 GPa) as compare to bulk modulus (178 GPa) is depicting the eminence of the former within the stability of a material. The bulk and shear modulus has also been calculated for other alloys and obtained results are comparable with Mn2CoP, Mn2CoAs [13], Mn2CoCr [16], Mn2PtCo [17], Rh2MnZr, Rh2MnHf [25] Rh2FeGa, and Rh2FeIn [26], Heusler alloys. The Pugh's ratio (B/G) defines the brittleness and ductility in a material that rely upon its equilibrium value (1.75).…”
Section: Rhsupporting
confidence: 58%
“…Recently, the structural, elastic, mechanical, electronic, optical properties of PbSnO 3 cubic perovskite compound have been studied under pressure by Noor et al 49 Such physical properties are fabulous in other materials too. [50][51][52] In addition to these well-known features, in this investigation, the electronic, thermoelectric and thermal characteristics of PbSnO 3 using DFT have been explored. Motivated by the fact that certain properties of this material like elastic, mechanical, thermoelectric and thermal are yet to be investigated with different exchange correlations.…”
Section: Introductionmentioning
confidence: 99%
“…[65] The elastic and mechanical results including melting temperature are given in Table 2 and are found to be in good agreement with the available results. [38,39,66,67] Further, Cu 2 MnAl-type structured Rh 2 MnX (X = Sc, Ti, Zr) full-Heusler alloys have been studied for thermal results using Gibbs model. [53][54][55] The various thermodynamic parameters like Debye temperature (θ D ), bulk modulus (B), and unit cell volume (V ) have been studied for the under temperature (0-1200 K) and pressure (0-20 GPa).…”
Section: Elastic Mechanical Stability and Thermodynamic Propertiesmentioning
confidence: 99%
“…In last decade, Heusler alloys have remained attention center especially for their magneto-electronic, elasto-mechanical, thermal, and thermo-electronic transport results. [38][39][40][41][42] From the previous discussion, it is clear that Heusler alloys have great potential in spin electronics and waste heat management. Recently, Mentefa et al [43] have reported the first-principles investigation of Rh 2 MnZ (Z = Zr, Hf ).…”
Section: Introductionmentioning
confidence: 99%